The Use of α-Diazo-γ-butyrolactams in the Büchner–Curtius–Schlotterbeck Reaction of Cyclic Ketones Opens New Entry to Spirocyclic Pyrrolidones - Eremeyeva, Maria; Zhukovsky, Daniil; Dar’in, Dmitry; Krasavin, Mikhail (Synlett, 2020)
The only cyclic α-diazocarbonyl compound employed in the Büchner–Curtius–Schlotterbeck ring expansion of cyclic ketones to date was α-diazo-γ-butyrolactone. Encouraged by the recent success using α-diazo acetamides in related Tiffeneau–Demjanov type ring expansions, we extended this approach to various α-diazo-γ-butyrolactams, which produced, under BF3·OEt2-promoted conditions, spirocyclic seven-membered ketones. These findings substantially enhance the possibilities offered by cyclic α-diazocarbonyl compounds in constructing privileged spirocyclic scaffolds for drug design.
Keywords: α-diazocarbonyl compounds; α-diazo-γ-butyrolactams; Büchner–Curtius–Schlotterbeck reaction; ring expansion; spirocyclic 2-pyrrolidones